Membrane localization of actin filaments stabilizes giant unilamellar vesicles against external deforming forces - Fink, Andreas; Fazliev, Sunnatullo; Abele, Tobias; Spatz, Joachim P.; Göpfrich, Kerstin; Cavalcanti-Adam, Elisabetta A. (European journal of cell biology, 2024)
Actin organization is crucial for establishing cell polarity, which influences processes such as directed cell motility and division. Despite its critical role in living organisms, achieving similar polarity in synthetic cells remains challenging. In this study, we employ a bottom-up approach to investigate how molecular crowders facilitate the formation of cortex-like actin networks and how these networks localize and organize based on membrane shape. Using giant unilamellar vesicles (GUVs) as models for cell membranes, we show that actin filaments can arrange along the membrane to form cortex-like structures. Notably, this organization is achieved using only actin and crowders as a minimal set of components. We utilize surface micropatterning to examine actin filament organization in deformed GUVs adhered to various pattern shapes. Our findings indicate that at the periphery of spherical GUVs, actin bundles align along the membrane. However, in highly curved regions of adhered GUVs, actin bundles avoid crossing the highly curved edges perpendicular to the adhesion site and instead remain in the lower curved regions by aligning parallel to the micropatterned surface. Furthermore, the actin bundles increase the stiffness of the GUVs, effectively counteracting strong deformations when GUVs adhere to micropatterns. This finding is corroborated by real-time deformability cytometry on GUVs with synthetic actin cortices. By precisely manipulating the shape of GUVs, our study provides a minimal system to investigate the interplay between actin structures and the membrane. Our findings provide insights into the spatial organization of actin structures within crowded environments, specifically inside GUVs that resemble the size and shape of cells. This study advances our understanding of actin network organization and functionality within cell-sized compartments.
Online verfügbar: 4. Juni 2024, Artikelversion: 7. Juni 2024
Gesehen am 19.12.2024